Vitamin D Status Among Patients With Dry Eye Syndrome Attended In Bangabandhu Sheikh Mujib Medical University (BSMMU) - Sajj , Abir Bin; Islam, Md Adnan; Sharmin, Tohura; Ahmed, Md Sharfuddin; Kabir, Md Showkat (The Journal of Ad-din Women’s Medical College, 2023)
Background: Dry eye syndrome (DES) is a common ocular manifestation. Artificial tears provide relief of eye irritation in patients with aqueous tear deficiency, but do not treat the underlying inflammation in Dry eye syndrome. Aim: To assess the vitamin D status of the dry eye syndrome patients. Methodology: This cross-sectional study was conducted in the Department of Community Ophthalmology, BSMMU, Shahbag, Dhaka, from July 2019 to June 2020. Within the period a total of 50 cases of dry eye syndrome patients that met the inclusion criteria were taken as samples after receiving their informed consent. Detailed history, physical examination and Ophthalmological examination including Tear film Breakup Time (TBUT) of each patient was performed and recorded. Eye discomfort was assessed by the Ocular Surface Disease Index (OSDI) the score of which ranges from 0 to 100. A score of 12 was used as a cutoff for normal, 13–22 for mild dry eye, 23–32 for moderate dry eye, and ≥ 33 for severe dry eye. Tear film Breakup Time (TBUT) <10 s was taken as abnormal. Results: In this study, mean (±SD) fluorescein Tear film Breakup Time (TBUT) was 5.89±1.31 sec, Schirmer test without anesthesia was 7.45±2.31mm/5 min, Schirmer test with anesthesia was 9.06±2.06mm/5 min and Ocular Surface Disease Index (OSDI) was 34.44±5.64. Mean (±SD) serum vitamin D level ng/mL was 5.89±1.31 ng/mL. 14 (28%) cases were found as insufficient, 33 (66%) cases were deficient and only 3 (6%) cases found to have normal Vitamin D status. Vitamin D level was positively correlated with Tear Breakup Time (TBUT), Schirmer test1 and Schirmer test2 and negatively correlated with OSDI. This correlation was statistically significant for Tear film Breakup Time (TBUT), Schirmer test2 and Ocular Surface Disease Index (OSDI). Conclusion: Vitamin-D deficiency appears to have an effect on ocular surface parameters in patients with dry eye syndrome. The Journal of Ad-din Women's Medical College; Vol. 11 (2), July 2023; p 3-8